(3hUjI GdfHi Udi Gddg Ydjg hSdes - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3bGd MOKfG GdTjN Gdabjg GdNWjH CHh WGdH Hf YHO GdZaGQ Hf CMeO Hf UGdM Cf QShd Gddg Udi Gddg Ydjg hSde hYdi Bdg bGd dCejQ GdeDefjf Ydi UdhGJ Gddg Ydjg Efi dhUjc HhUjg aGMaXgG s
(3BNQgG (B:s
(3hMb Ydi Gddg Cf dGjYPH MHjSg ai CQVg jG Ydi EMaX hUjJi hCfJ eY GdMa hGdMb eYc JeJ GdhUjI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs